Challenges faced by SMEs in their digital transformation towards Industry 4.0 - Kowalska, Katarzyna; Kowalik, Izabela (Contemporary organisation and management. Challenges and trends, 2020)
The article presents exploratory research that is aimed at identifying the challenges existing in the process of stimulating cross-industry collaboration between European agri-food, packaging and ICT SMEs in their digital transformation towards Industry 4.0. Taking as an example the European Strategic Cluster Partnership for smart investments called DIGICLUSTERS, the article presents qualitative research based on a single case study. The case examines a cluster-facilitated, agile approach to speeding up the prototyping and implementation of digital innovations in agri-food and packaging companies. Within this framework, the article shows that fostering cross-industry cooperation between traditional and hi-tech companies operating in clusters brings several benefits, but also entails technological, financial and managerial challenges. The originality of this article is in its examination of cross-industry hackathons as a new collaboration tool to stimulate digital innovations in agri-food and packaging SMEs towards Industry 4.0.